A cylindrical-core fiber-optic oxygen sensor based on fluorescence quenching of a platinum complex immobilized in a polymer matrix - Chen, R; Farmery, A; Obeid, A; Hahn, C (2012)
A miniature (200 μm in diameter) cylindrical-core fiber-optic oxygen sensor has been developed for measuring rapid change in oxygen partial pressure (pO 2). The fiber-optic sensing element is based on a cylindrical-core waveguide structure formed by coating a thin medical grade polymer sensing film that contains immobilized Pt(II) complexes on silica optical fiber. The performance such as sensitivity and time response of the fiber-optic oxygen sensors were evaluated using luminescence intensity measurement. To determine accurately the response time of the fiber-optic oxygen sensors, a test chamber was used to provide rapid changes in the partial pressure of oxygen. The result showed that the time response (time-constant, τ) of this cylindrical-core fiber-optic oxygen sensor is less than 50 ms. To our knowledge, this is the fastest such sensor of this size covering the full dynamic range of pO2 from 0 to 100 kPa. © 2006 IEEE.